The prevalence, risk factors and outcomes of workplace bullying among junior doctors: a systematic review - Samsudin, Ely Zarina; Isahak, Marzuki; Rampal, Sanjay (Taylor & Francis, 2018)
Junior doctors’ exposure to bullying may impact their training and compromise quality healthcare, yet little is known in relation to its predictors and effects. The aim of this paper is to assess the prevalence, factors and outcomes of workplace bullying among junior doctors. Literature search was performed to identify all primary studies examining workplace bullying among junior doctors using the following electronic databases: Medline, Scopus, Web of Science, PsycINFO and Cochrane Library. A total of 18 articles were included, reporting on a total of 9,597 junior doctors. The quality of evidence can be rated as moderate according to the Newcastle Ottawa Scale. From the review, a wide range (30–95%) of bullying prevalence, significant differences in bullying rates according to gender, age, height, ethnicity and subspecialty, and significant associations between bullying and mental strain, job dissatisfaction, burnout, and increased accidents at work were observed. Concurrently, heterogeneity in the terms and methodologies used to examine workplace bullying as well as definitional issues in relation to the persistency of negative interactions were noted. Evidence suggests that workplace bullying is a serious occupational hazard for junior doctors, and more research is warranted to better understand this phenomenon and address its definitional and methodological issues.